Waste tire derived char supported Ni‐Fe catalyst for catalytic thermochemical conversion of wet municipal solid waste. (28th October 2021) - Irfan, Muhammad; Li, Aimin; Zhang, Lei; Liu, Jianhua; Farooqi, Tanzeel Javaid Aini; Javid, Muhammad; Rauf, Abdul
Summary: Thermochemical conversion technology (pyrolysis/gasification) has been extensively employed for biomass, fossil fuels, and MSW feedstock to transform them into valuable products (gas, oil, and char). Since the practical application of waste tire derived char (WTC) faces uncertainty, the exploitation of WTC's high‐value application would significantly impact the overall economy of the waste tire pyrolysis process. Therefore, in this study, WTC was utilized as a support material for developing Ni‐Fe‐based catalysts (Ni‐WTC, Fe‐WTC, and Ni‐Fe‐WTC). The catalyst performance for wet MSW catalytic conversion was studied in a fixed‐bed reactor. The results affirmed that the application of catalysts considerably boosted the H2 concentration (29.26% to 38.24%‐42.15%), dry gas yield (0.73 to 1.04‐1.16 Nm 3 /kg MSW), and H2 yield (212 to 396‐487 mL/g MSW). Meanwhile, the tar content reduced significantly from 9.11% (without catalyst) to 2.15%, (Ni‐WTC), 2.83% (Fe‐WTC), and 2.47% (Ni‐Fe‐WTC). The tar analysis indicated that the chemical composition significantly transformed with the application of catalysts. This work successfully suggested that WTCs can be used as an effective and inexpensive support material for developing Ni‐based catalysts that can offer greater opportunity toward tar and hydrocarbons catalytic cracking and reforming during MSW conversion.